Role Analysis of E-Learning Program in Physical Learning - Mayub, Afrizal (Jurnal Pendidikan IPA Indonesia, 2018)
This study aimed to find out the application of e-learning program, the role of e-learning program and how important the role of e-learning program in Physics learning is. The method used included the creation of e-learning program through the stage of analyzing, designing, program writing and program testing. The sample used consisted of Chemistry study program students of odd semester of academic period of 2014/2015 and 2015/2016 which amounted to 80 people. From the data processing, it was revealed that e-learning program can be applied through e-learning modules, the role of e-learning program was in the category of "moderately contribute" with the score of 3.44 (scale 1 -5). While the relation between e-learning program with its role in Fundamental of Physics learning based on the theoretical mean for the category of moderate + high/strong + very high/very strong was equal to 91.25%, while for low/weak category was equal to 8.75%. However, if based on realistic mean for category of moderate + high/strong + very high/very strong was equal to 76.25%, whereas for category of low/weak and very low/very weak was equal to 23.75%.